Pengaruh Pupuk Organik Dari Cangkang Telur Ayam terhadap Pertumbuhan Tanaman Pala (Miristica fragrans Houtt) di Kota Ternate - Rosita Tabaika (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2021)
Chicken egg shell is one of the wastes that can be recycled and is very easy to find in everyday life because it is the basic ingredient of various foods and cakes that can be used as a product so that it can reduce and protect the environment from waste. Dried egg shells contain about 95% calcium carbonate with a weight of 5.5 grams. Calcium carbonate (CaCO3) in agriculture is used to accelerate the growth process in plants and as a plant pest control. The high calcium carbonate content of chicken egg shells can be used as a source of nutrients for plants, one of which is the Myristica fragrans Houtt plant. The objectives are 1). Analyzing the effect of organic fertilizer from chicken egg shells on the growth of Miristica fragrans Houtt. 2). Analyzing the levels of organic fertilizer from chicken egg shells that have the most effect in accelerating the growth of Miristica fragrans Houtt plants. The type in this research is quantitative research with experimental methods. This study used a randomized block design (RAK) consisting of 8 treatments and 5 replications. The research results are 1). There was a significant effect of organic fertilizer from chicken egg shells on the growth of Miristica fragrans Houtt plants for plant height, while the number of leaves, leaf length and leaf width had no significant effect. 2). The level of organic fertilizer from chicken egg shells that had the most effect on plant height, number of leaves, leaf length and leaf width of the Myristica fragrans Houtt plant was 25 grams.